Measurement and simulation of neutron monitor count rate dependence on surrounding structure. Issue 7 (6th July 2015) - Aiemsa‐ad, N.; Ruffolo, D.; Sáiz, A.; Mangeard, P.‐S.; Nutaro, T.; Nuntiyakul, W.; Kamyan, N.; Khumlumlert, T.; Krüger, H.; Moraal, H.; Bieber, J. W.; Clem, J.; et al.
Abstract: Neutron monitors are the premier instruments for precise measurements of time variations (e.g., of solar origin) in the galactic cosmic ray (GCR) flux in the range of ∼1–100 GeV. However, it has proven challenging to accurately determine the yield function (effective area) versus rigidity in order to relate a neutron monitor's count rate with those of other monitors worldwide and the underlying GCR spectrum. Monte Carlo simulations of the yield function have been developed, but there have been few opportunities to validate these observationally, especially regarding the particular environment surrounding each monitor. Here we have precisely measured the count rate of a calibration neutron monitor near the Princess Sirindhorn Neutron Monitor (PSNM) at Doi Inthanon, Thailand (18.59 ∘ N, 98.49 ∘ E, 2560 m altitude), which provides a basis for comparison with count rates of other neutron monitors worldwide that are similarly calibrated. We directly measured the effect of surrounding structure by operating the calibrator outside and inside the building. Using Monte Carlo simulations, we clarify differences in response of the calibrator and PSNM, as well as the calibrator outside and inside the building. The dependence of the calibrator count rate on surrounding structure can be attributed to its sensitivity to neutrons of 0.5–10 MeV and a shift of sensitivity to nucleons of higher energy when placed inside the building. Simulated calibrator to PSNM count rate ratios inside and outside agree with observations within a few percent, providing useful validation and improving confidence in our ability to model the yield function for a neutron monitor station. Key Points: At the Doi Inthanon neutron monitor (NM), we operated a calibration (Cal) NM We directly measured the Cal/NM count rate ratio dependence on surroundings Monte Carlo Cal/NM results match data to a few percent for different Cal locations